(untitled) (Scientific journal of the Fergana State University, 2025)
n Alfred Adler’s views, the focus is not only on the relationship between the social-economic structure of society and an individual’s personal existence, but also on the emergence of a reverse perception in the human psyche in relation to the economic situation, which has been studied.